Fatal air embolism during gastrointestinal endoscopy in a 5 -year- old girl - Kalagi Dana; Alalawi Shahd; Al Shawa M. Anas; Habib Zakaria (Elsevier, 2021)
Introduction: Gastrointestinal endoscopy and endoscopic retrograde cholangiopancreatography (ERCP) are generally considered safe procedures with very minimal complications. However, they can be associated with uncommon yet life-threatening complications such as air embolism. Case presentation: A 5-year-old female was referred to our hospital for the evaluation of a left upper quadrant mass. The patient underwent exploratory laparotomy, and a biopsy was obtained. Histopathology confirmed the diagnosis of ganglioneuroblastoma. The patient afterwards underwent laparotomy, and tumor excision resulted in an iatrogenic injury to the superior mesenteric artery, leading to ischemic enteritis requiring multiple small bowel resections resulting in short bowel syndrome and small bowel strictures; gastrointestinal endoscopy was needed for dilatation. Unfortunately, during endoscopy, the patient developed air embolism and went into cardiac arrest. Then an urgent central venoarterial extracorporeal membrane oxygenation (ECMO) was deployed, and the patient was shifted to the intensive care unit and died a few hours later. Conclusion: Air embolism is considered a very rare yet fatal complication of endoscopy. The exact mechanism behind air embolism will differ from one patient to another, making it challenging to identify it. It is important to anticipate such complication in high-risk patients, and all precautions must be taken when performing endoscopic procedures.